Sea Quest - Borden, Charles A.; Busoni, Rafaello, 1900-1962 (Philadelphia : Macrae smith, 1967)
An introduction to the island world of the Pacific.
Cover title: Oceania : Hawaii, New Zealand and the South Pacific.
Maps on lining papers.
Includes Index.
Keywords: Oceania